Femtosecond laser-induced surface structuring of the porous transport layers in proton exchange membrane water electrolysis. Issue 9 (24th February 2020) - Suermann, Michel; Gimpel, Thomas; Bühre, Lena V.; Schade, Wolfgang; Bensmann, Boris; Hanke-Rauschenbach, Richard
Abstract : Experimentally determined reduction of both ohmic and mass transport overpotential due to femtosecond laser-induced surface structuring of titanium-based porous transport layers at the interface to the catalyst layer. Abstract : In proton exchange membrane water electrolysis (PEMWE) cells the performance and thus the conversion efficiency are influenced by the interface between the porous transport layer (PTL) and the catalyst layer (CL). In the following paper, this interface is modified by the use of femtosecond laser-induced surface structuring, so that the specific surface area of the titanium based fibers of the PTL is increased. The resulting morphology exhibits two roughness levels of (i) a relatively coarse structure featuring tips of a few micrometers in diameter and depth, which are each covered in turn by (ii) a substructure of smaller tips of a few to several hundred nanometers in diameter and depth. PEMWE electrochemical characterization and short-term stress tests reveal that the cell performance is increased due to the laser-structuring of the PTL surface towards the CL. For instance, the cell voltage is reduced by approximately 30 mV after 100 h at 4 A cm −2 . These beneficial effects are observed over the entire current density range and thus correspond to a decreased equivalent cell resistance of at least 6 mΩ cm 2 for electrical interfacial contact losses and at least 2 mΩ cm 2 for mass transport losses. A physical characterization by scanning electron microscopy shows that the CL surface is much rougher and more jagged when using laser-structured fibers. Thus, the gaseous oxygen and the liquid water transport both from and to the active sites of the catalyst seem to be improved.